Prognoza zmian postępowania z osadami ściekowymi w świetle krajowego programu gospodarki odpadami = Prognosis of change in sewage sludge utilization methods accordance to KPGO (Polish Waste Management Planning) - Węclewski, Sebastian (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article presents the prognosis for the coming years, concerning the changes in the neutralization methods of sewage sludges in accordance to Polish Waste Management Planning. The further evolution the methods for sewage sludge handling in Poland will depend on their quality and legal conditions.
Keywords: 3 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: zrównoważona gospodarka zasobami naturalnymi" (24-25.06.2004)